Editor's Choice – Durability of Endovascular Repair in Blunt Traumatic Thoracic Aortic Injury: Long-Term Outcome from Four Tertiary Referral Centers. Issue 4 (October 2015) - Steuer, J.; Björck, M.; Sonesson, B.; Resch, T.; Dias, N.; Hultgren, R.; Tunesi, R.; Wanhainen, A.; Lachat, M.; Pfammatter, T.
Abstract : Objectives: To analyze the early and long-term survival and re-intervention rate in patients undergoing TEVAR for blunt traumatic thoracic aortic injury. Methods: This was a consecutive case series. Between the years 2001 and 2010, a total of 74 patients underwent TEVAR for blunt traumatic thoracic aortic injury at four tertiary referral centers, three in Sweden and one in Switzerland. The median age of the patients was 41 years, and 16% were women. Demographic, procedural, and outcome data were collected and reviewed retrospectively. The patients were followed up during 2013–2014. Results: Early (30 day) mortality was 9% (7 patients), with only two cases directly related to the aortic injury; in hospital mortality was 14% as three patients died during the primary hospital admission within the first 6 months. Most patients had sustained severe injuries to other organ systems, and among all in hospital deaths brain injury was the predominant cause. Five year survival in the whole group was 81%. Re-intervention was needed in 16% (12 patients) during the first year, half of them within the first month. Only one patient underwent re-intervention more than 1 year after the initial procedure. Infolding and partial stentgraft collapse was the reason for the secondary procedure in five of the 13 patients; in three it occurred within 3 weeks of the acute TEVAR. Conclusion: TEVAR allows rapid and effective therapy in trauma patients with blunt aortic injury. The outcome is dependent on the severity of the concomitant injuries. The treatment is durable during the first decade after the procedure, but even longer follow up is needed to determine the impact of TEVAR in young patients on the degenerative changes that take place in the aging aorta.